There Comes Papa; Colonialism and the Transformation of Matriliny in Kerala, Malabar c. 1850-1940 - Arunima, G (Hyderabad, 2003)
This is the first study to examine Nayar matriliny as a historical phenomenon. Kerala is the only place in the world where a kinship system was outlawed! The book analyses the reasons for the abolition by the colonial state and lays bare the differences between early twentieth, late twentieth and mid-nineteenth century forms of matriliny. This is the first historical work in India on matriliny.
Keywords: Colonialism-Kerala